Ecological Aspect of Pidada (Soneratia caseolaris Linn. Engler, 1987) at Muara Angke, Jakarta - Nyoto Santoso; Cecep Kusmana; Dedi Sudarma; Rinekso Sukmadi (Jurnal Manajemen Hutan Tropika, 2007)
Pidada (Sonneratia caseolaris Linn. Engler, 1987) and parepat (Sonneratia alba J. Smith) are central genetic of species and genus Sonneratia.  Hight growth plant of pidada was 18.5-42 cm/month, and diameter growth of trees was 1.75-3.45 cm/month, roots growth was faster (10-20 cm/ 16 month) on substrads with deep mudy (> 1 m) depenth of substrats with sallow mudy or hard soils. Presentase of life plant pidada (spacing 1 x 1 m) was 70 % (trees age was 6 months), 60 % (1 years) and 18 % (6 years).  Seeds number of pidada fruits was723 - 1,768 seeds/fruits. Pest of pidada plants usually species of insect groups that attact trees, and disease was viruses that attack on leaves.Keyword: